The influence of sex on high intensity swimming test - Moreno Lara, Javier; López León, Inmaculada; Leitão, Luís; Fernandes da Silva, Sandro; Sánchez-Oliver, Antonio Jesús; Domínguez, Raúl (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Differences based on sex have been reported in the energetic and mechanical demands of different exercise modalities; however, no studies have analyzed the influence of sex during high-intensity swimming. The aim of this study was to determine sex-based differences in the response to a high intensity swimming test on performance, fatigue, blood lactate concentrations (BLa) and rating of perceived exertion (RPE). A total of 23 competitive swimmers (11 males; 12 females) performed 8 sets of 50-m at maximum intensity with 2 minutes of recovery intra-sets. Pre- and post-exercise, BLa was analysed. In addition, RPE were administered at the end of each 50-m. Differences were detected in the high intensity swimming test on sex (η²p=0.566; p<0.001) and time (η²p=0.233; p<0.001), but not for the interaction time·sex (p>0.05). It was reported an effect for time on BLa (η²p=0.947; p<0.001) and RPE (η²p=0.559; p<0.001), but not for sex nor the interaction time·sex (p>0.05). Although males are faster, not differences were found in BLa, fatigue nor RPE between sexes. These results could be mediated by the all-out nature of the protocol and practical implications suggest that it is not necessary to adapt the training load in high intensity swimming session attending to the sex of the athletes.